The willingness of tourism-friendly cities' representatives to share innovative solutions in the form of open innovations - Adam R. Szromek; Bartłomiej Walas; Zygmunt Kruczek (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The tendency of enterprises to use open innovations can be seen in the literature in many areas of research and practical application. However, the use of the concept of open innovation in local administration entities is less noticeable. The research gap in this area prompts the authors to examine such a tendency among city representatives in the example of the Tourism Friendly Cities (TFC) group. TFC is a group of nine tourism destinations that are also European cities struggling with the impact of modern tourism. They take part in the URBACT program under the European Territorial Cooperation program. The goal of the article is to identify the basic problems of TFCs with the impact of the COVID-19 pandemic and to assess the propensity of TFC representatives to transfer innovative solutions in the form of open innovation. The article presents findings based on interviews with 104 experts from these cities, consisting of representatives of the public and private sectors. Research results indicate that the key problems of modern tourism in TFCs include constraints related to the lack of parking spaces, high rents and high prices of land, and short-term rental housing. The experts recommend measures to increase resilience and competitiveness initiated by business owners and at the initiative of the local administration. Key tools in this regard include and local community communication and engagement, creating attractions that benefit both residents and visitors, and measuring and monitoring tourism. In all, 92.8% of the experts believe that the right solution for the development of methods and tools for stakeholder cooperation in TFCs is to share the developed solutions in the form of open innovation.
Keywords: 650; experts; open innovation; overtourism; qualitative research; tourism; tourism friendly cities